Prevalence and Factors associated with Dental Caries among Adolescents aged 12-15 years in Rural communities in Enugu, Southeast Nigeria (Update Dental College Journal, 2026)
Background: Dental caries can affects all socioeconomic class and it continues to be of dental public health interest.Objective: To determine the prevalence and factors associated with dental caries among adolescents aged 12-15 years in four rural communities in Enugu, Southeast NigeriaMethods: A cross sectional descriptive study among 12-15 years old was carried out in Nkanu–West and Udi local Government Area of Enugu State. Data collection was done in 2024. Socio-demographic data was obtained using semi--structured questionnaire.. Oral examination for the presence of dental caries was done by two examiners using the DMFT index. Tests of association between dependent variable (dental caries) and independent variables (age, sex, socio-economic status, oral hygiene status, tooth-brushing frequency and use of fluoride containing toothpaste) were conducted using Chi square/fisher exact test. Statistical analysis was done using SPSS Version 25. p